2015
DOI: 10.1292/jvms.14-0290
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence for influenza virus infection in Korean wild boars

Abstract: Serum samples from 1,011 wild boars hunted in 2012 were collected for serological surveillance for 4 subtypes (pandemic A (H1N1) 2009 and classical H1N1, H1N2 and H3N2) of swine influenza virus (SIV). Samples from 12 of the boars were identified as positive for SIV (pandemic A (H1N1) 2009, n=9; classical H1N1, n=2; and H1N2, n=1) by a hemagglutination inhibition test (HI test) and a nucleoprotein (NP)-based enzyme-linked immunosorbent assay (NP-ELISA). Although the overall seroprevalence of SIV in the Korean w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Virus‐neutralization tests demonstrated that IAVs whose HA and NA are antigenically closely related to the H1N1pdm09 virus were predominantly distributed in Japanese wild boar populations in Kagoshima prefecture, Japan. After the spread of the H1N1pdm09 virus and their reassortant strains in human and domestic pig populations worldwide, the percentage of wild boars seropositive against pandemic‐related strains was found to be much higher than those against other subtypes of IAVs . Several studies have shown that multiple subtypes of IAVs infections, including H1N1, H1N2, and H3N2, have been diagnosed in wild boars .…”
Section: Summary Of the Results Of Serological Test Using Virus‐neutrmentioning
confidence: 89%
See 1 more Smart Citation
“…Virus‐neutralization tests demonstrated that IAVs whose HA and NA are antigenically closely related to the H1N1pdm09 virus were predominantly distributed in Japanese wild boar populations in Kagoshima prefecture, Japan. After the spread of the H1N1pdm09 virus and their reassortant strains in human and domestic pig populations worldwide, the percentage of wild boars seropositive against pandemic‐related strains was found to be much higher than those against other subtypes of IAVs . Several studies have shown that multiple subtypes of IAVs infections, including H1N1, H1N2, and H3N2, have been diagnosed in wild boars .…”
Section: Summary Of the Results Of Serological Test Using Virus‐neutrmentioning
confidence: 89%
“…After the spread of the H1N1pdm09 virus and their reassortant strains in human and domestic pig populations worldwide, the percentage of wild boars seropositive against pandemic-related strains was found to be much higher than those against other subtypes of IAVs. 8,9 Several studies have shown that multiple subtypes of IAVs infections, including H1N1, H1N2, and H3N2, have been diagnosed in wild boars. [8][9][10][11] These serological surveys suggest that wild boars can serve as mixing vessels for IAVs, and potential sources for novel pandemic strains.…”
mentioning
confidence: 99%
“…The seroprevalence of IAV among wild boars varies from 0% in Finland, France and Slovenia, up to 74% in China [ 1 , 3 , 8 , 19 , 22 , 23 ]. In this study, the seroprevalence of IAV in wild boars was lower than in domestic pigs (8.4–22.7%) in Japan [ 18 ].…”
mentioning
confidence: 99%
“…Confirmed infection is notifiable to OIE. Consistent with this concern is the identification in wild suids of both avian and human influenza virus infections including pandemic H1N1 2009, classical H1N1, H1N2, H3N2 (Biondo et al, 2014;Cano-Manuel et al, 2014;Cho et al, 2015;Foni et al, 2013;Kaden et al, 2008;Perera et al, 2013;Shimoda et al, 2017;Touloudi et al, 2015;Vicente et al, 2002). In one study, H1N2 virus was associated with bronchopneumonia in boars; however, it is unknown if the virus was contributory, as IHC was negative for influenza A and positive for Mycoplasma hyopneumoniae (Biondo et al, 2014).…”
Section: Rna Virusesmentioning
confidence: 96%